2017
DOI: 10.3892/or.2017.5835
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-379 acts as a tumor suppressor in non-small cell lung cancer by targeting the IGF-1R-mediated AKT and ERK pathways

Abstract: Lung cancer is one of the most common types of malignancy in humans and is a leading cause of cancer-related deaths among men and women worldwide. Aberrantly expressed microRNAs in non-small cell lung cancer (NSCLC) contribute to tumor occurrence and development as either tumor suppressors or promoters. MicroRNA-379 (miR‑379) is dysregulated in several types of human cancer. However, its expression pattern, role and underlying mechanism in NSCLC progression and metastasis are poorly understood. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…These results suggested that GCNT3 and miR-302b-3p affect NSCLC metastasis partly via the EMT. In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggested that GCNT3 and miR-302b-3p affect NSCLC metastasis partly via the EMT. In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Erk signaling pathway has been shown to be frequently activated in numerous kinds of human cancers [43][44][45]. Aberrant activation of phosphorylated Erk1/2 induced by miRNAs has been observed in lung cancer [45][46][47]. Recent reports point out that miR-379 acts as a tumor [45], miR-7 inhibits the activation of ERK/MAPK signaling pathway by down-regulating FAK expression [46], and miR-622 overexpression decreases invasion in lung tumor cells by inhibiting HIF-1alpha via inactivation of ERK signaling in A549 cell [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars further validated the up-regulated expression level of miR-379-5p in cell line model and speculated the translocation of miR-379-5p from cancer cells to circulation might contribute to the high-regulation of miR-379-5p in circulation exosomal samples (34). Similar conditions were also reported in lung cancer (35,36). This suggested the profiling of miRNAs in circulating exosome may have a great difference with those in tissue or blood.…”
Section: Discussionmentioning
confidence: 55%
“…The pathogenic mechanisms underlying the development of cancer, including CRC, are heterogeneous and regulated by multiple signaling pathways, including PI3K/AKT and ERK[25,26]. Previous studies have reported that the PI3K/AKT and ERK signaling pathways regulate cell growth, apoptosis and metastasis[46]. As one of the important intracellular signal transduction pathways, PI3K/AKT signaling has been reported to play important roles in cell survival, apoptosis and metastasis [47].…”
Section: Discussionmentioning
confidence: 99%